Accountability of Village Fund Management As an Effort to Accelerate the Achievement of Village SDGs - Pramono Sari, Maylia; Yulianto, Agung; Mussanadah, Atik Ul; Arumawan, Mei Saputra; Raharja, Surya (Universitas Negeri Semarang, 2025)
Village fund management requires oversight to ensure financial accountability and reduce the potential for irregularities. In accordance with Law No. 6 of 2014 on Villages, the allocation of village funds reflects the government’s commitment to fostering independent, progressive, and democratic rural communities. Giling Village, Pabelan District, Semarang Regency, continues to face non-compliance with Minister of Home Affairs Regulation (Permendagri) No. 20 of 2018 and encounters challenges within its Village-Owned Enterprise (BUMDes), particularly in organizational structuring, legal formalization, and adherence to Good Corporate Governance (GCG) principles. The community service program consists of three main components: (1) identifying gaps in the Village SDGs; (2) facilitating the official registration of BUMDes to ensure regulatory compliance; and (3) delivering training on financial accountability and GCG in village fund management. These efforts are expected to increase progress in achieving village SDGs, especially in the areas of economic empowerment and sustainable development. . Mapping results show that the village has achieved 41% of its SDG indicators. The highest priorities fall under Typology III (health) and Typology V (education), while the lowest priorities are found in Typology IV (environment) and Typology VII (networked village). Through structured financial governance, the legal transformation of BUMDes, and capacity-building initiatives for village administrators, the program aims to strengthen financial transparency, accountability, and sustainable economic empowerment in the village.